Use of BIM technology in project coordination: a case study in residential building - Oliveira, Jamile Cristine de Souza; Tavares, Thayná Cavalcante; Silva Neto, Dimas de Castro e (Brazilian Journal of Production Engineering, 2025)
Project coordination helps to prevent inconsistencies among disciplines but is often limited when conducted using two-dimensional tools. This study examined the use of Building Information Modeling (BIM) technology to identify clashes between architectural, structural, and plumbing designs in a single-family residential building. The methodology involved creating 3D models using Revit software and performing clash detection in Navisworks with the Clash Detective tool. A total of 72 clashes were identified: 31 between architectural and structural elements, and 41 between structural components and plumbing systems. Some conflicts were resolved through minor modeling adjustments, while others—especially those involving piping—required route modifications and revisions to structural elements. The results suggest that 3D modeling supports early detection of design issues, helping to reduce rework and inform technical decisions. Although limited to a single case, the findings align with previous research on BIM in construction and point to practical advantages for project coordination.